1-P-D-5. Anti-GT1a antibody characteristics in Miller Fisher syndrome with or without sensory nerve conduction abnormalities. Issue 6 (June 2015) - Nagashima, Takahide; Kokubun, Norito; Okamura, Madoka; Komagamine, Tomoko; Hirata, Koichi; Yuki, Nobuhiro
<x xml:space="preserve">Abstract</x> To clarify the immunological and clinical features, the antibody specificities were analyzed in Miller Fisher syndrome (MFS) with and without sensory nerve conduction abnormalities. Anti-ganglioside antibodies and anti-ganglioside complex (GSC) antibodies coordinated with GT1a were analyzed in 17 MFS patients. Clinical features including the nerve conduction study results were also reviewed. All 17 MFS patients (median age, 52 years [10 men and 7 women]) had ophthalmoparesis, ataxia, and decreased tendon reflexes. 9 of 17 of the patients presented one or more nerves with abnormal sensory conduction in the median, ulnar or sural nerves. Anti-GQ1b and anti-GT1a antibodies were detected in 13 and 10 patients, respectively. Anti-GSC antibodies were detected in 8. All of 9 patients with abnormal sensory conduction had anti-GQ1b or -GT1a antibodies. In 8 patients with normal sensory conduction, 5 had anti-GQ1b or -GT1a antibodies. Anti-GT1a/GA1 complex antibody was frequent in patients with normal sensory conduction compared with the patients with abnormal sensory conduction. In 9 of 10 patients with anti-GT1a antibody, the activity of the antibodies to GT1a was higher than those to GSC. In MFS, the antibody with strong specificity to GT1a can be correlated with sensory nerve conduction abnormalities.